Genetic diversity and structure of the Chinese lake gudgeon (Sarcocheilichthys sinensis). (17th August 2020) - Ding, Xin-Hua; Hsu, Kui-Ching; Tang, Wen-Qiao; Liu, Dong; Ju, Yu-Min; Lin, Hung-Du; Yang, Jin-Quan
Abstract: Mitochondrial DNA cytochrome b and d-loop sequences (2, 137 bp) in 65 specimens of Sarcocheilichthys sinensis from five populations were identified as two lineages (I and II). The pairwise genetic distance between lineages I and II was 1.94%. SAMOVA analyses suggested that the best grouping occurred at three groups, Yangtze, Qiantang and Minjiang Rivers. High haplotype diversity (0.949) and low nucleotide diversity ( θ π = 1.067%) were detected. The results of the neutrality tests, mismatch distribution and approximate Bayesian computation (ABC) did not support demographic expansions. The results of phylogenetic analysis, statistical dispersal-vicariance analysis (S-DIVA), ABC, MIGRATE-N and the time to the most recent common ancestor (TMRCA ) indicated two colonization routes. First, before the Wuyi Mountains lifted, S. sinensis dispersed from the Yangtze River to the Minjiang River. Second, during glaciation, the continental shelf was exposed, which contributed to the dispersion of populations from the Yangtze River.